Comparing the Chemical Characteristics of Pectin Isolated from Various Indonesian Fruit Peels - Siti Susanti; Anang Mohamad Legowo; Nurwantoro Nurwantoro; Silviana Silviana; Fahmi Arifan (Universitas Gadjah Mada, 2021)
The Indonesian pectin manufacturing industry is underdeveloped, and pectin is imported to meet its increasing demand; we attempted to isolate pectins from various fruit peels, such as orange peel (OP), papaya peel (PP), mango peel (MP), watermelon peel (WP), and chayote peel (CP) and investigated their chemical characteristics (equivalent weight of the extracted pectins and their moisture, ash, methoxyl, and galacturonic acid (GA) contents). Acid extraction, purification, precipitation, and drying processes were used to process the isolated pectins. We examined their chemical properties for conformance to quality standards advised by the International Pectin Producers Association (IPPA). The moisture (except OP pectin) and ash contents (except PP pectin) of the extracted pectins were within the limit set by IPPA. However, the equivalent weight (W eq) of any of the isolated pectins did not satisfy IPPA standards. The methoxyl contents of the pectins isolated from OP, WP, and CP satisfied IPPA standards. High methoxyl pectins were isolated from PP and MP. The galacturonic acid contents of the isolated pectins were higher than the acceptable limit of the GA level. Thus, OP, PP, MP, WP, and CP are potential sources of pectin.